KUALITAS AUDIO VISUAL PROGRAM SEPUTAR INDONESIA MENENTUKAN BRAND ACTIVATION DI MASYARAKAT - Eko Febrianto (Universitas Mercu Buana, 2016)
Abstract: Competition attracts and seizes the viewers' sympathy nowadays is getting tighter, every televisionstation keeps making breakthrough creative programs, which can bring viewers and financial benefits,including news programs. To get the attention of the viewers, every editor of the news program team definitelyneeds certain ways and strategies, so that the results of the coverage presented and processed can be acceptedand watched as many audiences or audience. Therefore, audio visual quality and creativity is needed in packingnews programs. Audio visual quality also keeps viewers from switching to other news programs so that the goalof reaching as many audiences can be achieved. Audio visual quality can be obtained from hard work andcreativity redaction choosing sound and image and pack it optimally, in order to compete with other newsprograms. Good audio visual quality including by adding graphics, immersive and motion and supported byaudio, so it becomes part in the process of brand activation television station in the eyes of viewers. Researchwith Postpositivism paradigm is raised about how a process Audio Visual news program can affect BrandActivation or reputation and reputation of the company. The entire production team ranging from field teams,editors in charge, to marketing from the company has a major role in strengthening the good image of thecompany through the Audio Visual program presented.Key Words: Audio Visual Quality, News Program, Brand Action